First-Time Finds: Eight Rare Mushroom Species in Kurdistan's Wilderness - Nareen Q. FaqeAbdulla; Hero M. Ismael; Musa I. Taha; Farid M. Toma; Sanar A. Suleman (Zanco Journal of Pure and Applied Sciences, 2024)
Seventeen mushroom species from fourteen genera were collected and identified from various locations, such as: Bardarash, Barzan, Erbil city center, Hiran, Mergasor, Shaqlawa, Khalefan, Tawska and Taqtaq. The following genus and species have been identified: Agaricus bisporus, A. campestris, A. incultorum, Coprinus comatus, Lycoperdon umbrinum, Amanita virosa, Panaeolus semiovatus, Pleurotus ostreatus, Omphalina pyxidate, O. rosella, Phallus impudicus, Fomitopsis betulina, Ganoderma applanatum, Daedaleopsis confragosa, lactarius vellereus, Helvella leucopus and Bisporella citrina. Seven genera (8 species) of mushrooms were discovered for the first timein kurdistan region-Iraq, such as: Lycoperdon umbrinum, Amanita virosa, Omphalina pyxidate, O. rosella, Phallus impudicus, Daedaleopsis confragosa, Helvella leucopus and Bisporella citrina. The goal of this research is to investigate and identify wild mushrooms that naturally occur in the Erbil Governorate, Kurdistan Region of Iraq, in various areas and during various seasons.